Interrogative Modality in Spoken Language : An Exploration of the Use of Modality in Educational Discourse - Jatiswa, Bayu Anggara Riyan; Rosadi, Pendi; Muhaimi, Lalu; Hadi, Makmur (Universitas Cokroaminoto Palopo, 2025)
This study explores interrogative modality in educational discourse at SMA 7 Mataram, specifically in English language classrooms. The research aims to investigate how teachers utilize interrogative modality and to determine its impact on the learning process. Adopting a qualitative approach with a case study design, data were collected through classroom observations, audio recordings, and semi-structured interviews with four experienced English teachers. The analysis revealed that teachers employ diverse interrogative modalities, with